Comparison of the Effects of Nettle and Alyssum with Q10 Plus and L-Carnitine on Improving Sperm Parameters of Infertile Men (Bangladesh Journal of Medical Science, 2024)
Background Infertility is one of the most stressful and complicated experiences in a couple’s life.Objective The aim of this study was comparing the effects of Nettle and Alyssum with Q10 plus and L-Carnitine on improving the sperm parameters of infertile men in Iran.Materials and Methods This three-blind randomized clinical trial study conducted on 75 infertile men referred to Jahrom infertility clinic in 2022. The participants selected by simple random method and assigned to two intervention and control groups. The subjects of the intervention group took herbal drugs includes urtidine (Nettle) and Alyssum. The control group took routine treatment consists Q10 plus and l-carnitine for 12 weeks. Data collected through the standard checklist of semen analysis before and the end of the intervention for both groups. Data were analyzed by descriptive (frequency and percentage) and analytical (Fisher-exact, chisquare, independent t-test and Mann-Whitney U) tests.Results The results indicated that the positive effectiveness of Nettle and Alyssum on the improvement of some sperm parameters of infertile men, including volume, sperm shape and motility compared to Q10 plus and L-carnitine. In fact, after the intervention, a statistically significant difference observed in the parameters of sperm in in the intervention group compared to the control group (p